2021
DOI: 10.1002/admt.202001006
|View full text |Cite
|
Sign up to set email alerts
|

Design and Operation of Hybrid Microfluidic Iontronic Probes for Regulated Drug Delivery

Abstract: Highly controlled drug delivery devices play an increasingly important role in the development of new neuroengineering tools. Stringent—and sometimes contradicting—demands are placed on such devices, ranging from robustness in freestanding devices, to overall device miniaturization, while maintaining precise spatiotemporal control of delivery with high chemical specificity and high on/off ratio. Here, design principles of a hybrid microfluidic iontronic probe that uses flow for long‐range pressure‐driven trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…All parameter values were within biophysical ranges (Table 1 ) (Hille, 2001 ; Kandel et al, 1981 ). Recent experimental work, using selective ionic pumps to deliver locally K + , confirmed observations from the model, the elevation of [K + ] modified the spiking profile of a bursting neuron in the hippocampal slice (Arbring Sjöström et al, 2021 ). However, the model has two main limitations.…”
Section: Discussionmentioning
confidence: 68%
“…All parameter values were within biophysical ranges (Table 1 ) (Hille, 2001 ; Kandel et al, 1981 ). Recent experimental work, using selective ionic pumps to deliver locally K + , confirmed observations from the model, the elevation of [K + ] modified the spiking profile of a bursting neuron in the hippocampal slice (Arbring Sjöström et al, 2021 ). However, the model has two main limitations.…”
Section: Discussionmentioning
confidence: 68%
“…In 2021, Arbring Sjöström et al demonstrated a coaxial capillary device (for fluid inlet and outlet) with an “iontronic cap” featuring an AEM ion channel ( Figure 4 d). 74 With the PEDOT-based source electrode (cathode) incorporated onto the surface of the inner capillary, a minimal amount of wiring was needed to drive the device (the anodic counter electrode was a separate piece of PEDOT:PSS), making it simple to mount on a micromanipulator and integrate into a standard electrophysiology setup. Glutamate was delivered (as an anion) into artificial cerebrospinal fluid and used to demonstrate the spatiotemporal precision (via a glutamate biosensor), paving the way for application in brain slice models or as a depth probe.…”
Section: Chemical Stimulation and Drug Deliverymentioning
confidence: 99%
“…(d) Freestanding fluidic capillary-based device with “iontronic cap”. Parts a and d reproduced with permission from refs and , respectively. Copyright 2018 and 2021 John Wiley and Sons.…”
Section: Chemical Stimulation and Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…This is benecial for the stimulation of biological systems with minimal perturbation of the target environment. 133 However, an important operating condition for chemical stimulation with the OEIP is the application of a suitable electrochemical potential to prevent reactive oxygen species (ROS) generation. At low potentials within the ohmic region, the relationship between ionic current and voltage is linear.…”
Section: Chemical Stimulation Of Neural Systems Via Iontronic Devicesmentioning
confidence: 99%